Adjustment to retirement: effects of resource change on physical and psychological well-being - Yeung, Dannii Y. (Eur J Ageing, 2017)
A 1-year longitudinal study was conducted to examine the effects of retirement resources on the physical and psychological well-being of Hong Kong Chinese retirees during the transition to retirement. This study consisted of two assessments: Time 1 was conducted 6 months before retirement, while Time 2 was implemented 6 months after retirement. Personal resources and physical and psychological well-being were measured in the two assessments. The final sample contained 128 retirees who completed both assessments. Compared with Time 1, the retirees reported fewer financial resources at Time 2. Change in cognitive resources was significantly predictive of the changes in physical functioning, life satisfaction, psychological well-being, and psychological distress during the transition period. The findings of this longitudinal study reveal that in addition to financial, physical, and social resources that have often been emphasized in the past literature, mental resources also play an important role in positive adjustment to retirement. Future retirement planning programs are recommended to include modules for strengthening cognitive, emotional, and motivational resources of retired persons.